Group B Streptococcus Colonization among Pregnant Women Attending Antenatal Care at Tertiary Hospital in Rural Southwestern Uganda - Namugongo, Abdul; Bazira, Joel; Fajardot, Yarine; Joseph, Ngonzi (International journal of microbiology, 2016)
Objectives. This study sought to determine the prevalence and factors associated with group B streptococcal anogenital colonization among pregnant women attending antenatal care at Mbarara Regional Referral Hospital, a tertiary hospital. Methods. Crosssectional study where 309 pregnant women ≥ thirty-five weeks of gestation attending antenatal clinic were consecutively recruited between January and March 2015. Anovaginal swabs were collected and tested qualitatively using rapid visual immunoassay GBS test kits for presence of GBS antigens. Data was analyzed using STATA version 12. In univariate analysis, GBS colonized mothers were presented as percentages and numbers, and in multivariate analysis logistic regression analysis was applied to determine the associations of exposure variable andGBS colonization; a value of less than 0.05 was considered significant Results. Mothers’median age was 25 years, 14.6% mothers being obese. GBS prevalence was 28.8%, 95% CI: 23.7–33.9. Obesity was the only significant factor associated with anogenital GBS colonizationwith odds ratio of 3.78, 95% CI: 1.78–8.35, a 𝑝 value of 0.001.Maternal ages, educational level, residence, and gravidity were not associated with GBS anogenital colonization. Conclusion. Group B streptococcal anogenital colonization among pregnant women attending antenatal care at tertiary hospital, in Southwestern Uganda, is high.